Implementación de los Laboratorios Veterinarios de la UTC con Sistema de Gestión de Calidad (Norma NTE INEN-ISO/IEC 17025:2018). - Sandoval Valencia, Hugo Patricio (2023)
The implementation of a Quality Management System (QMS) with the ISO/IEC 17025:2018 Standard in the Veterinary Medicine Laboratory of the Technical University of Cotopaxi is a comprehensive process that seeks to ensure the technical suitability and quality of the services offered by the laboratory and its implementation provides a solid foundation to ensure the reliability of the results. In the case of the Laboratory of Veterinary Medicine of the Technical University of Cotopaxi, the implementation of the standard involves several important steps. First, by conducting a thorough analysis of the requirements indicated by the standard and evaluating the current state of the laboratory in relation to those requirements, the structures, procedures, and controls are established that ensure the reliability of the results and strengthen the position of the UTC laboratory in the academic and professional environment. The aim is to guarantee the reliability of the results of the tests carried out, which increases the confidence of the clients and users of the laboratory, whether they are from the veterinary clinic or those who are dedicated to productive species and who have an interest in the control of diseases of official health programmes, of those endemic, exotic, or re-emerging ones.